An investigation on student's conceptual understanding of newton's third law - force in equilibrium and attitudes in physics using EquiForce Kit with STAD cooperative learning - Chong, Chin Lu (2013)
The purposes of present study were to (I) investigate the effects of incorporating a manipulative material - 'EquiForce Kit' (EFK) in a Student Team-Achievement Division (STAD) classroom; and to (ii) examine students' attitudes toward Physics using EFK. A total of 77 students who take Physics subject In two secondary schools around Penampang and Kolombong district in Sabah were assigned into STAD (control group) and STAD-EFK (treatment group). Force in Equilibrium Concept Test (FECT) and Attitudes in Physics were used to collect data. The data was then analyzed using independent and paired sample t-test with SPSS 16.0. The finding indeed showed better improvement of conceptual understanding of Force in Equilibrium in STAD-EFK group than in STAD group, but the changes were not significant. Besides, the attitudes survey also indicated no significant difference in pre- and post-test of STAD-EFK group.